Robert Kearns’ Obsession in Fighting for Recognition in Flash of Genius Movie - Jerli Hasundungan; Priyoto Priyoto; Sahril Mujani (STIBA IEC JAKARTA, 2024)
The purpose of this study was to analyze know the causes of Robert Kearns the causes of Robert Kearns obsession to obsess in gaining recognition. This research uses qualitative methods. The object used in this study is a film namely Flash of Genius film. The data collected is obtained from the results of watching the film and sorting out the scenes and dialogues or utterances in the film. The results showed that Robert Kearns experienced some psychological problems which include having mind set all the time, self-doubt, Self-worth, Project delays and abandonment, steering clear of challenges and maintaining a facade at all times